Risk Selection under Public Health Insurance with Opt-out - Sebastian Panthöfer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper studies risk selection between public and private health insurance when some individuals can purchase private insurance by opting out of otherwise mandatory public insurance. Using a theoretical model, I show that public insurance is adversely selected when insurers and insureds are symmetrically informed about health-related risks, and that selection can be of any type (advantageous or adverse) when insureds have private information about health risks. Drawing on data from the German Socio-Economic Panel, I find that: (1) public insurance is adversely selected under the German public health insurance with opt-out scheme, (2) individuals adversely select public insurance based on self-assessed health and advantageously select public insurance based on risk aversion, and (3) there is evidence of asymmetric information.
Keywords: I13; D82; H51; 330